Condições de vida e saúde de moradores em um “acampamento sem-teto” no município de Maceió-AL - Cavalcanti, Rita de Cássia Camêlo Bueno (2009)
In recent decades, there has been an advance in the study of the relationships between the way a given society is organized and developed and its health situation. In many regions, it is possible to observe health inequalities between population groups. The relationships between health and its determinants establish hierarchies between factors of a socio-economic, political-cultural and environmental nature, in the context in which individuals live and work. Although these determinants influence lifestyles and condition the individual to belong to this or that social group, they will have an impact on the determination of health standards, both individual and group. We developed a qualitative research, in a homeless camp, located in the peripheral region of the city of Maceió / Alagoas, with the following objectives: to know the lengthy living and health conditions and how they deal with health issues; trace the socio-demographic profile of the population studied. The sample consisted of 15 women, including the leader of the camp and some residents who showed interest in collaborating with the research. We applied two questionnaires, the first with closed questions and the second of a qualitative nature. The analysis of the data of the closed questions detected the socio-demographic profile of the residents. The analysis of data from open questions used the Content Analysis method. The results showed us that in the camp the living conditions are below those recommended by the International Conferences on Health Promotion. The results indicated that the houses are poorly ventilated, without basic sanitation and electricity, with a dirt floor. When they show signs or symptoms of illness, they use drugs, already known to them. Sometimes they seek health care in public health units, posts and hospitals. Families are not registered with the PSF. The women interviewed showed great hope that the situation will improve with the donation of houses promised by the government four years ago.